Effect Of Vitamin E On Oxidative Stress Indicated By Serum Malondialdehyde And Paroxonase Level In Type 2 Diabetes Mellitus With Retinopathy (Journal of Pharmaceutical Negative Results, 2023)
Background In type 2 diabetes mellitus, the body gradually loses its ability to produce adequate insulin from the pancreas and/or becomes resistant to the typical effects of insulin.Objectives This case-control study was carried out to evaluate the impact of vitamin E on oxidative stress in T2DM patients with retinopathy as measured by malondialdehyde and paronxanase 1 levels.Subjects and Methods This study was conducted over a period of 11 months on thirty diabetic patients divided into two equal groups; the first group had T2DM without retinopathy (control), while the second group had T2DM with retinopathy (case). Ophthalmological evaluation, Serum paraoxonase-1 and malondialdehyde levels, after 12-hour fasting, blood samples were taken to estimate all laboratory investigation. Results In the group of participants with T2DM and retinopathy, there was a statistically significant positive correlation between the paroxanase 1 level and HDL. Additionally, the T2DM with retinopathy group's paroxanase 1 level increased statistically significantly after receiving antioxidant vitamin E treatment for three months. Conclusion Serum MDA levels were related to DR stage, indicating that oxidative stress is a major factor in the development of DR. However, proliferative DR patients' MDA levels dropped after taking vitamin E for three months.